Development and Use of Mobile Containment Units for the Evaluation and Treatment of Potential Ebola Virus Disease Patients in a United States Hospital. (21st April 2015) - Sugalski, Gregory; Murano, Tiffany; Fox, Adam; Rosania, Anthony; Bogucki, Sandy
Abstract Ebola virus disease (EVD) has been the subject of recent attention due to the current outbreak in West Africa, as well as the appearance of a number of cases within the United States. The presence of EVD patients in the United States required health care systems to prepare for the identification and management of both patients under investigation and patients with confirmed EVD infection. This article discusses the development and use of a mobile containment unit in an extended treatment area as a novel approach to isolation and screening of potential EVD patients.